2016
DOI: 10.18632/oncotarget.9701
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals that distant recurrence-associated protein R-Ras and Transgelin predict post-surgical survival in patients with Stage III colorectal cancer

Abstract: Surgical resection supplemented with adjuvant chemotherapy is the current preferred treatment for Stage III colorectal cancer (CRC). However, as many as 48% of patients who undergo curative resection eventually suffer from incurable distant recurrence. To investigate the molecular mechanisms involved in Stage III CRC post-surgical distant recurrence, we identified a total of 146 differentially expressed proteins (DEPs) associated with distant recurrence in Stage III CRC using TMT-based quantitative mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Liquid chromatography–mass spectrometry/mass spectrometry (LC-MS/MS) was performed as described previously 46 , 47 with slight modifications. The peptide mixture was separated with the EASY-nLC 1000 system equipped with a homemade fused silica capillary column (75 μm ID, 150 mm length; Upchurch, Oak Harbor, WA, USA) packed with C-18 resin (300 A, 5 μm; Varian, Lexington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Liquid chromatography–mass spectrometry/mass spectrometry (LC-MS/MS) was performed as described previously 46 , 47 with slight modifications. The peptide mixture was separated with the EASY-nLC 1000 system equipped with a homemade fused silica capillary column (75 μm ID, 150 mm length; Upchurch, Oak Harbor, WA, USA) packed with C-18 resin (300 A, 5 μm; Varian, Lexington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…TMT labeling was performed as described previously with slight modifications . Briefly, six samples from three sporadic MTC patients were pooled as Group A (mixed tumorous tissues) and Group B (mixed paired normal thyroid tissues).…”
Section: Methodsmentioning
confidence: 99%
“…Li et al ( 26 ) demonstrated that SM22α may decrease proliferation and invasion, and increase apoptosis in colorectal carcinoma cells. Xu et al ( 27 ) reported that SM22α may prevent the metastasis of CRC. These findings indicate that SM22α may act as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%